Usage of computer algebra in teaching process - Domarkas, Aleksas; Misevičius, Gintautas; Pakalnytė, Violeta; Pincevičius, Albertas; Rakauskas, Rimantas-Jonas (Lietuvos matematikos rinkinys, 1998)
This work was intended to motivate the necessity of intensive training of mathematics utilising the computer algebra MAPLE in Lithuanian Military Academy. Such trend is promising because it gives the possibility to combine the teaching of classical mathematics with theory of informatics. Modern computer algebra is able to solve the typical problems of higher mathematics teaching in universities and academies or another high schools. We analyse the principals subjects. Where one can get the best efficiency in utilising the computer algebra. Namely, it is the problems of linear algebra, analyse of graphs, numerical calculation, integration, solution of differential equations, statistics for management, linear programming. The authors share his experience of utilising of computer algebra to effect the education of cadets. One can have a lot of examples of utilising of computer algebra in the manual of higher mathematics (with supplementary disquiet) to be appeared.